<> chivalric life - Jacques,Brown-Grant, Rosalind,Damen, Mario (The Boydell Press, 2022)
The first English translation of the chivalric biography of the foremost knight of the late Middle Ages
10.1017/9781800105928
Keywords: Kommentar; Jacques de Lalaing / 1423-1453 / Histoire du bon cheualier